Bio-Inspired Hierarchical Micro/Nanostructured Surfaces for Superhydrophobic and Anti-Ice Applications - Zhang, Lansheng; Uzoma, Paul C.; Xiaoyang, Chu; Penkov, Oleksiy V.; Hu, Huan (Frontiers in Bioengineering and Biotechnology, 2022)
We report a scalable and cost-effective fabrication approach for constructing bio-inspired micro/nanostructured surfaces. It involves silicon microstructure etching using a deep reactive ion etch (DRIE) method, nanowires deposition via glancing angle deposition (GLAD) process, and fluorocarbon thin film deposition. Compared with the smooth, microstructured, and nanostructured surfaces, the hierarchical micro/nanostructured surfaces obtained via this method showed the highest water contact angle of ⁓161° and a low sliding angle of ˂10°. It also offered long ice delay times of 2313 s and 1658 s at –5°C and –10°C respectively, more than 10 times longer than smooth surfaces indicating excellent anti-icing properties and offering promising applications in low-temperature environments. These analyses further proved that the surface structures have a significant influence on surface wettability and anti-icing behavior. Hence, the GLAD process which is versatile and cost-effective offers the freedom of constructing nanostructures on top of microstructures to achieve the required objective in the fabrication of micro/nanostructured surfaces when compared to other fabrication techniques.